Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis jaquinensis) Terhadap Pemupukan Phospor Dan Dolomit - Purwati Purwati (Universitas Widya Gama Mahakam, 2012)
The research aimed to identify the growing of seedling Elaeis jaquinensis on Phospor fertilizer and Dolomit Application, as well as its interaction, and to find the proper concentration of Phospor fertilizer for seedling Elaeis jaquinensis. This research lasted for four months, from Oktober2010to Januari 2011, at the Village of Sempaja Sub District of Samarinda. The research was designed in Completely Randomized Block Design with Factorial 3 x 4 and three replications. The first factor comporised of 3 levels of Phospor dosage (1,5, 2,0 and 2,5 g SP-36/polybag and the second factor was dolomit dosage (0,10, 15 and 20 g dolomit/polybag. The results showed that: (1) significant responses the phosphor fertilizer on the parameters of number of leaf at the stage of 90 old days and diameter of stemat the stage of 60 old days; (2) significant responses on the Dolomiton the parameters of diameter of stemat the stage of 30 and 60 old days; (3) significant responses the interaction between phospor fertilizer and Dolomit application on the parameter of number of leaf at the stage of 60 old days. Kelapa Sawit (Elaeis jaquinensis), phospor fertilizer, dolomite